Inhibitory properties of Enterococcus spp. isolated from faeces of healthy dogs - Fernandez Juri, Maria Guillermina (2013)
The aim of the present study was to evaluate the inhibitory effect by the cross-streak method of nine Enterococcus faecium strains isolated from faeces of healthy dogs and their treated and non-treated cell-free supernatant (CFS) by the well-diffusion test on the growth of potentially pathogenic bacteria isolated from clinical cases and aflatoxigenic Aspergillus section Flavi and the consequent aflatoxin B1 (AFB1) production. Results obtained from the cross-strake assay showed that E. faecium MF1, GJ18 and GJ40 presented the major inhibitory activity against all pathogenic strains assayed; E. faecium GJ40 produced the larger inhibitory zones (26–27 mm). Well-diffusion test results showed that the majority of the enterococci strains CFS had antimicrobial activity against the pathogenic microorganisms, especially on Gram negative indicators. Cell-free supernatant of E. faecium GJ40 was the one that produced the largest inhibition zones (14 to 21 mm) in the majority of the indicator microorganisms assayed. All supernatants treated with 10 N NaOH (pH6) showed no inhibitory effect on the indicator strain assayed. With respect to fungal inhibition, any of the CFS assayed significantly inhibited the Aspergillus strains growth. But, in general, all CFS reduced AFB1 production from 8 to 87%. The results demonstrate that enterococci isolated from healthy dog feaces produce substances with the capacity to inhibit some potential pathogenic bacteria growth and the capacity of inhibiting or reducing the AFB1 production in vitro.